Larvicidal activity of crude extracts from Larrea cuneifolia (Zygophyllaceae) and of its metabolite nordihydroguaiaretic acid against the vector Culex quinquefasciatus (Diptera: Culicidae) - Gonzalo Batallán; Romina Torre; Fernando Flores; Brenda Konigheim; Francisco Ludueña-Almeida; Carlos Tonn; Marta Contigiani; Walter Almirón (Revista da Sociedade Brasileira de Medicina Tropical, 2013)
INTRODUCTION: The aim of the present study was to analyze the larvicidal activity of different crude extracts of Larrea cuneifolia and its most abundant lignan, nordihydroguaiaretic acid (NDGA), against Culex quinquefasciatus. METHODS: Chloroform, methanol, and aqueous extracts from L. cuneifolia and NDGA were tested against larvae of Cx. quinquefasciatus under laboratory conditions. RESULTS: The chloroform extract showed the highest larvicidal effect, with an estimated LC50 of 0.062 mg/ml. NDGA also demonstrated significant larvicidal activity with an estimated LC50 of 0.092 mg/ml. CONCLUSIONS: These results indicate that the chloroform extract of L. cuneifolia and NDGA are promising insecticides of botanical origin that could be useful for controlling Cx. quinquefasciatus.